Radiodocumentário “A outra voz do Amazonas”: A história do rádio em Parintins e a contribuição sociopolítica da Rádio Clube - Bezerra, Rebeca Gonçalves (Brasil, 2023)
The present work presents a study on the radio that has always been one of the main means of communication in the world, with the title ''Radiodocumentary The other voice of the Amazon: The history of radio in Parintins and the sociopolitical contribution of Rádio Clube'', which brings a bit of the broadcaster as one of those elements that drive Amazonian education. Which aims to show the contribution of radio to the Amazon and, more specifically, in the sociopolitical development of cities and rural areas where the station has reached, identifying the context of the transformations of Parintinense society from the socio-educational influence of the station . The scientific research is of a qualitative nature and has bibliographical research as procedures. It had its theoretical foundation based on the following authors; Corrêa (2022), Frederico (2007), Ferraretto (2007), Gil (2002), Oliveira e Monteiro (2017), Souza (2021), Prodanov and Freitas (2013), Silva and Menezes (2005) among others who supported this search. With this study from this production we can say that the sociopolitical role of the radios has been effective in the sociopolitical construction of Parintins, which Rádio Clube directly contributes to this development from the moment that it seeks the inclusion of other manifestations of popular culture, religions , movements and communities. In a process of secularization, this breaks hegemony and enables the democratization of education via radio. Therefore, this research can contribute to the scientific, academic, social and professional fields of journalism.